(untitled) (Revista de Investigaciones Universidad del Quindío, 2016)
Colombia has always been a well-known country in terms of natural resources. In particular, mineral resources have become more and more relevant, because of the interest in oil exploitation. However, the easy-access zones are running out of oil, and the efforts are shifting and focusing towards the exploration of hard-access zones. In order to explore these hard-access zones looking for hydrocarbons, economical and reliable alternative techniques are required. Seismic tomography is one of them, which allows obtaining sub surface velocity models from seismic acquisitions performed on the Earth’s surface. There are several tools developed for performing seismic tomography. One of them is FMTOMO, which is a tool that solves seismic tomography as an inverse problem, dealing with it as an optimization problem proposed from a linear approximation of the Eikonal equation. The main focus of this work is to evaluate the results obtained using FMTOMO and computing performance. At the end, it is presented a summary of its strengths and weaknesses.